Critical success factors of Malaysian Armed Forces digital library system / Abdul Rahim Abdul Rahman - Abdul Rahim , Abdul Rahman (2021)
Digital Library System (DLS) refers to an online database that collects, creates, stores, distributes, and preserves digital objects, including text, images, video, and audio over a network. The present study aims to understand the critical success factors affecting user satisfaction and their continuous usage intention behaviour. This study employed updated DeLone and McLean IS Success Model (ISSM) and incorporated additional construct, namely perceived instrumental support to predict the critical success factors of Malaysian Armed Forces Digital Library System (MAFDLS). This study employed survey questionnaires to examine the research model and hypotheses developed. Five hundred twenty-four usable responses from military members who have accessed and used the digital library system were analysed using SPSS 25 and PLS 3.2.9. Within the context of military setting, it appears that perceived quality experience and perceived instrumental support as critical factors that triggered user satisfaction, net benefits and continuous usage intention behaviour. The findings specifically support that user satisfaction and net benefits play as sequential mediating roles between the perceived quality experience and continuous usage intention. In this study, perceived instrumental support affects user satisfaction and continuous usage and plays a moderating role between perceived quality experiences and user satisfaction. Hence, it is safe to say that users who are not satisfied with the system due to imperfect perceived quality experience factors would experience low difficulties. This study's perceived quality factors were MAF digital library environment, information relevance, system accessibility, navigation, and interface design. If they receive necessary instrumental supports from Malaysian Armed Forces Digital Library (MAFDL), this would increase users' perceptions of perceived instrumental support factors (such as education and training; technical support and communication support). While it is vital to satisfy the users' needs and satisfaction, Malaysian Armed Forces Digital Library (MAFDL) needs to bear in mind that not all group of users are the same. This study found that the different group specifics (such as geographical locations, level of experience and type of usage) have model effect differences as evidence to support that different group specifics have different perceptions of the overall digital library system evaluation criteria unique needs and opinions. The findings also uncover the potential challenges and issues faced by users when using the system. The results were synthesised, which would assist the management by re-strategizing the overall service delivery system by improving WebOPAC, KnowledgeBased Taxonomy, and MAF e-resource embedded in the system. The researcher produced strategic, tactical, and operational planning for future digital library system improvements based on full sampling or re-sampling group findings. Thus, the various planning of various levels of Malaysian Armed Forces (MAF) libraries was translated into a management action plan that acted as key performance indicators. This management action plan ensures that the military-users' needs are met to achieve a higher level of satisfaction on quality and instrumental support factors. It also meant getting higher organisational and individual impacts that benefit the users in having the system and having higher overall service delivery. In the end, it also meant to improve the continuous usage intention behaviour as the proxy to success behaviour of Malaysian Armed Forces Digital Library System (MAFDLS) future usage.